Proton pump inhibitor usage reduces sustained viral response rates for veterans with HIV/HCV coinfection on ledipasvir/sofosbuvir: a real‐world study from a multicentre VA cohort. Issue 4 (28th January 2021) - Lee, Tzu‐Hao; Chan, Austin; Bryan, William; Park, Lawrence; Hashem, Mohamed; Townsend, Mary; Moylan, Cynthia; Britt, Rachel; Choi, Steve; Naggie, Susanna
Abstract: Previous studies have reported an association of proton pump inhibitor (PPI) use and decreased sustained viral response rate (SVR) in patients taking ledipasvir/sofosbuvir (LDV/SOF). The relationship between PPI usage and SVR is less clear in patients with HIV/HCV coinfection, where concomitant antiretrovirals may result in more complex drug interactions. This retrospective study evaluates the effects of acid suppression medications (PPI or H2 ‐receptor antagonist [H2 B]) use and SVR rates in patients with HIV/HCV or HCV and taking LDV/SOF in a large multicentre veteran cohort. Patients in the Veterans Affairs Health Care System who received LDV/SOF ± ribavirin from 10/10/2014 to 12/31/2015 were included. The odds ratios (OR) of PPI or H2 B use for SVR were adjusted for clinical factors and with inverse probability of treatment weighting for non‐random treatment selection for acid suppression medication use. There were 9703 veterans included in our final analysis. After adjustment of other clinical factors, PPI use is associated with a lower SVR in the overall cohort (95.0% vs. 96.1%, OR: 0.86, 95% CI: 0.74–0.99, p  = .03, number needed to harm 90.9) and HIV/HCV coinfection subgroup (93.4% vs. 96.9%, OR: 0.47, 95% CI: 0.26–0.85, p  = .01, number needed to harm 28.6). This present study reveals PPI use is associated with reduced SVR after LDV/SOF treatment, with a more significant impact in the subgroup of patients with HIV/HCV coinfection. Precautions need to be taken when using PPI and LDV/SOF in this group of patients.